Pengaruh Pelatihan Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Maan Ghodaqo Shiddiq Lestari Jombang - Ahmad Rodli Alfarisi (BIMA : Journal of Business and Innovation Management, 2022)
Thiss study aims to find out the effectof work training anddwork environment onn employee performance in PT. Maan Ghodaqo Shiddiq Lestari Jombang. Themethod and used in this study is quantitative, the sample in this study was takeen by 60 respondent usiing the questionnaire distribution method using the saturated sampling technique. The results show that : (1) work training has no positive and significant effect on employee performance in PT Maan Ghodaqo Shiddiq Lestari Jombang, (2) Work environment partially positive and significant effect on employee performance variables in PT Maan Ghodaaqo Shiddiq Lestari Jombang, (3) work training and work environment have a simultaneous effect onemployee performaance in PT.iMaan Ghodaqo Shiddiq Leestari Jombang. Keyword : Job Training; Work Environment; Worker; Performmance